2018
DOI: 10.1016/j.psep.2018.06.035
|View full text |Cite
|
Sign up to set email alerts
|

Industrial wastewater treatment through bioaugmentation

Abstract: Bioaugmentation of activated sludge processes through the addition of microorganisms is employed with the aim of enhancing treatment, in particular the removal of priority pollutants. With industrial wastewaters, studies have covered target pollutants including ammonia and polycyclic aromatic hydrocarbons (PAHs): compounds that are regulated around the globe. However, bioaugmentation is a technique that has been associated with doubt in regard to its ability to benefit treatment processes. Failure of bioaugmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
35
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(38 citation statements)
references
References 74 publications
0
35
0
3
Order By: Relevance
“…This approach increases the acclimated biomass by adding supplementary microorganisms to the natural biosystems, which can enhance the response of the microbial communities to specific environments or toxic pollutants. A series of studies using bioaugmentation to improve degradation of highly toxic and recalcitrant wastewater showed that bioaugmentation can effectively increase the steady‐state removal rate, reduce the shock loading impact of toxic compounds and decrease the time required for the degradation process . Many approaches for bioaugmentation in secondary biochemical treatment have been developed, but few studies have reported their application in a BAF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach increases the acclimated biomass by adding supplementary microorganisms to the natural biosystems, which can enhance the response of the microbial communities to specific environments or toxic pollutants. A series of studies using bioaugmentation to improve degradation of highly toxic and recalcitrant wastewater showed that bioaugmentation can effectively increase the steady‐state removal rate, reduce the shock loading impact of toxic compounds and decrease the time required for the degradation process . Many approaches for bioaugmentation in secondary biochemical treatment have been developed, but few studies have reported their application in a BAF.…”
Section: Introductionmentioning
confidence: 99%
“…A series of studies using bioaugmentation to improve degradation of highly toxic and recalcitrant wastewater showed that bioaugmentation can effectively increase the steady-state removal rate, reduce the shock loading impact of toxic compounds and decrease the time required for the degradation process. [28][29][30] Many approaches for bioaugmentation in secondary biochemical treatment have been developed, but few studies have reported their application in a BAF.…”
Section: Introductionmentioning
confidence: 99%
“…Physicochemical and biological treatments are among the most widely used methods [21]. us, they have been the subject of several research projects [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, establishing wastewater treatment which is economically acceptable and has a low ecological footprint is highly important. For this reason, biological processes are being applied in treatment of a wide range of industrial wastewater; activated sludge has been identified as the best available technique for achieving required emission limit values . Industrial wastewater contains a broad spectrum of different compounds that can be degradation‐resistant and stay unchanged in wastewaters treated with the activated sludge process.…”
Section: Introductionmentioning
confidence: 99%